1998
DOI: 10.1038/sj.onc.1201972
|View full text |Cite
|
Sign up to set email alerts
|

Src kinases and not JAKs activate STATs during IL-3 induced myeloid cell proliferation

Abstract: Interaction of IL-3 with its receptor is known to activate STAT-3 via phosphorylation of Tyrosine 701, which facilitates its dimerization and translocation to the nucleus, leading to the transcription of its target genes. In this communication, we have investigated the nature of tyrosine kinases that mediate STAT-3 phosphorylation during IL-3-mediated activation of myeloid cell proliferation. Our results show that interaction of IL-3 with its receptor leads to the activation of c-Src kinase activity, which in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
123
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 27 publications
(48 reference statements)
7
123
1
1
Order By: Relevance
“…In this study, we found G-CSF-mediated STAT phosphorylation is not Lyn-dependent by means of antisense JAK or AG490 inhibition experiments. Consistent with this, overexpression of dominant-negative JAK2 had no effect on Srcmediated phosphorylation of STATs (Chaturvedi et al, 1998). Combined with our results, this suggests that two independent pathways exist that mediate STAT activation, one dependent on the JAKs and the other dependent on Src kinases.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found G-CSF-mediated STAT phosphorylation is not Lyn-dependent by means of antisense JAK or AG490 inhibition experiments. Consistent with this, overexpression of dominant-negative JAK2 had no effect on Srcmediated phosphorylation of STATs (Chaturvedi et al, 1998). Combined with our results, this suggests that two independent pathways exist that mediate STAT activation, one dependent on the JAKs and the other dependent on Src kinases.…”
Section: Discussionsupporting
confidence: 90%
“…Several groups have reported that v-src and Src-kinase can activate STAT3 (Cao et al, 1996;Campbell et al, 1997;Chaturvedi et al, 1998). In addition, Marrero et al (1995) reported that activation of STAT3 can be induced or enhanced by GCRs, in particular by angiotensin II AT 1 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…As STAT3 has been shown to regulate mitogenesis or/and prevention of cell apoptosis in various cell types (Fukada et al, 1996;Chaturvedi et al, 1998) and 85 kDa STAT3D proteins are overexpressed in a i2 -G204A and a i2 -G204A/v-fms cells, we investigated whether excessive STAT3D expression inhibits NIH3T3 cell proliferation. Cells stably transfected with STAT3D55C cDNA showed increased expression of 85 kDa STAT3D (Figure 8), but also, as observed previously (Kim and Baumann, 1997), a slightly decreased expression of 89 kDa STAT3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations